A CITY ON WATERS: USE AND QUALITY OF THE GROUNDWATER IN MOSSORÓ-RN - Peixoto, Filipe da Silva; Tôrres, Lucas Matheus Garcia; Ferreira, Isabel Cristina Silva; Silva, Anderson Mikael de Souza (Geosaberes; Vol 12 (2021), 2021)
Mossoró city has water supply from groundwater (70%), capitated in their urban zone, however, there is not current registers end basic information of the wells, mealy bad information about water quality. The current study aimed identify use and quality of the groundwater, and hydrogeological aspects descriptions. For this, we constructed wells register with data from Information System of Groundwater – SIAGAS/CPRM, and Companhia de Águas e Esgoto do Rio Grande do Norte – CAERN. We evidenced the Apodi Aquifer System – AAS constituted for Barreiras aquifer, with function of the transference of water to Jandaíra aquifer, characterized as unconfined as karstic, Quebradas aquitard, forming a confidant to semi-confinant layer for Açu aquifer. This is the most productive and has good quality waters for several uses but has been presented decrease of the water quality.